2021
DOI: 10.1088/1361-6463/abd1a3
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of experiment and model for reactive HiPIMS: effect of discharge parameters on WOx composition and deposition rate

Abstract: Reactive high-power impulse magnetron sputtering of tungsten oxide films using metallic tungsten target (72 mm in diameter) in argon-oxygen atmosphere (total pressure of 0.75 Pa) was carried out. The effect of various discharge parameters on the deposition rate and film oxygen concentration was investigated. Moreover, a model combining a reactive high-power impulse magnetron sputtering model and a discharge plasma model for the ionization region was successfully used for deeper insight into the effect of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
3
1
Order By: Relevance
“…As a consequence, the fraction of implanted oxygen ions and atoms decreases with pulse duration and the oxygen composition of the SSL becomes smaller for long compared to short pulses. Calculations by Rezek et al also show a decrease of the target oxide fraction as function of pulse length [18]. However, the calculated decline is rather weak and quantitatively deviates from our observations.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…As a consequence, the fraction of implanted oxygen ions and atoms decreases with pulse duration and the oxygen composition of the SSL becomes smaller for long compared to short pulses. Calculations by Rezek et al also show a decrease of the target oxide fraction as function of pulse length [18]. However, the calculated decline is rather weak and quantitatively deviates from our observations.…”
Section: Discussioncontrasting
confidence: 91%
“…For a typical discharge current of 10 A, the surface coverage reduces within 54 µs by half (θ = 0.5) and to less than θ = 0.12 within 200 µs. The surface coverage is a pronounced function of the discharge current (power) which is in line with calculations performed by Rezek et al [18] who concluded that the O/W flux ratio decreases with increasing discharge power. The surface coverage recovers during the off time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tungsten (7.98 V) has a higher ionization potential than Cu (7.73 V), Ti (6.83 V), and Al (5.99 V), and is therefore more difficult to ionize, while it has a sputter yield slightly higher than titanium, and has a higher atomic mass. Earlier, a volume-averaged model has been developed to describe a reactive HiPIMS discharge and to model the deposition of WO 3 films from a tungsten target in Ar/O 2 mixture [28]. The model results indicate that the degree of tungsten ionization increases from 50% to 80% as the power density is increased from 100-500 W cm −2 , and it also increases with increased pulse length.…”
Section: Introductionmentioning
confidence: 99%
“…The model results indicate that the degree of tungsten ionization increases from 50% to 80% as the power density is increased from 100-500 W cm −2 , and it also increases with increased pulse length. Furthermore, it is claimed that W + ions are re-implanted into the target which effectively decreases the target oxide coverage during reactive sputtering [28].…”
Section: Introductionmentioning
confidence: 99%